2009
DOI: 10.1016/j.adolescence.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Are high school students living in lodgings at an increased risk for internalizing problems?

Abstract: This study aimed to investigate whether leaving home to live in lodgings during senior high school can be a risk factor for the development of internalizing problems. Utilizing two large‐scale prospective community studies of 2399 and 3906 Norwegian students (age range 15–19 years), respectively, the difference in internalizing symptoms between adolescents living in lodgings and adolescents living with their parents during senior high school was examined. Female students living in lodgings had higher scores on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The present study shows a significant difference between the t-test means of the private and the government group in items such as: the permission to go out, permission to go home when possible and permission for having parties. According to Wannebo and Wichstrom (2010), social support is found to be directly related to mental health, and to act as a buffer in stressful times (Compas, Slavin, Wagner, & Vannatta, 1986;Herman-Stahl & Petersen, 1999). Denying the students permission to go home when possible, permission to going out or having parties is akin to denying them social support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study shows a significant difference between the t-test means of the private and the government group in items such as: the permission to go out, permission to go home when possible and permission for having parties. According to Wannebo and Wichstrom (2010), social support is found to be directly related to mental health, and to act as a buffer in stressful times (Compas, Slavin, Wagner, & Vannatta, 1986;Herman-Stahl & Petersen, 1999). Denying the students permission to go home when possible, permission to going out or having parties is akin to denying them social support.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have focused upon the well being of students residing in school or college dorms. Indeed, research upon this area is a relatively new interest (Rogers & Tennison, 2009;Bell & Bromnick,1998;Wannebo & Wichstrom, 2010).…”
Section: The Role Of the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in mental health problems in adolescents, especially among girls, during the last 20 years has been identified (Bor, Dean, Najman, & Hayatbakhsh, 2014; Collishaw, 2015; Von Soest & Wichstrøm, 2014). Likewise, a Norwegian study found that students living in lodgings during senior high school were particularly vulnerable to stress and internalizing problems compared to students living with their parents (Wannebo & Wichstrøm, 2010). Few studies have been published on adolescents moving from home to attend school at such an early age.…”
Section: Introductionmentioning
confidence: 99%